Cardiac bypass pump flow management via NIRS monitoring. Issue 2 (2003) - Macnab Macnab, Andrew J. Andrew J.; Gagnon Gagnon, Roy E. Roy E.; Gagnon Gagnon, Faith A. Faith A.; Blackstock Blackstock, Derek Derek; LeBlanc LeBlanc, Jacques G. Jacques G.
Abstract : During cardiac surgery, bypass pumps rely on pressure monitors to evaluate flow. We studied whether it would be possible to optimize pump flow by monitoring changes in cerebral cytochrome a, a 3 using NIRS to maintain cyt redox status at its pre-bypass level. Method : 18 healthy 7–45 kg swine were placed on bypass for repeated cycles of cooling and re-warming from 36 to 15 to 36 ° C in 3 ° C steps. Between each cycle, the swine's bypass pump blood flow rate was adjusted to restore cytochrome redox status to its pre-bypass value. Results : In all swine trials, the number of pump flow alterations imposed by NIRS monitoring ranged from 0 to 42, the average being 14 per trial. The best trial had 22 pump flow adjustments during which the range of cytochrome redox status change was 0.50±0.06 μ mol l –1 . The average trial had a range of cytochrome redox status change of 1.50±0.22 μ mol l –1 . Conclusion : NIRS-driven alterations in pump flow rate to maintain pre-bypass cytochrome redox status can be achieved successfully in the animal model.